OsDOF11 Affects Nitrogen Metabolism by Sucrose Transport Signaling in Rice (Oryza sativa L.) - Huang, Xinglei; Zhang, Yiyan; Wang, Leilei; Dong, Xinyi; Hu, Weixin; Jiang, Min; Chen, Gang; An, Gynheung; Xiong, Fei; Wu, Yunfei (Frontiers in Plant Science, 2021)
Carbon and nitrogen antagonistically regulate multiple developmental processes. However, the molecular mechanism affecting nitrogen metabolism by sucrose transport remains poorly defined. Previously, we noted that Oryza sativa DNA BINDING WITH ONE FINGER 11 (OsDOF11) mediated sucrose transport by enhancing sucrose transporters. Here, we note that OsDOF11 promotes nitrogen uptake and then maintains the ratio of fresh weight to dry weight in seedling plants and the effective leaf blade at flowering stages. Mutants of the sucrose transporter gene Oryza sativa Sugars Will Eventually be Exported Transporters 14 (OsSWEET14) displayed a phenotype similar to that of OsDOF11. By microarray analysis and qRT-PCR in OsDOF11 mutant plants, OsDOF11 affected the transcription level of amino acid metabolism-related genes. We further found that mainly amino acid contents were reduced in flag leaves but increased in seeds. Both sugar and organic nitrogen changes caused the ratio of fresh weight to dry weight to decrease in OsDOF11 mutant seedling plants and mature leaves, which might result in vigorous reduced metabolic activity and become less susceptible to stress. These results demonstrated that OsDOF11 affected nitrogen metabolism by sugar distribution in rice, which provided new insight that OsDOF11 coordinated with C and N metabolism to maintain plant tissue activity by sucrose transport.